Analysis of the efficiency of different coverings with high thermal performance in control of hydrothermal comfort - Broggio, Lucas (Revista Hipótese, 2019)
The research analyzes the efficiency of the green curtain in decreasing temperature of the buildings and their influence on the comfort conditions. To measure these advantages, two environments were analyzed, with green curtain protection and another without. As a result, it offers a comparative database between the types of coverage analyzed, which assists decision making in building projects and also allows the replication of this research with different sustainable materials.